Not Just a Common Criminal : The Case for Sentencing Mitigation Videos - Austin, Regina (2014)
Sentencing mitigation or sentencing videos are a form of visual legal advocacy that is produced on behalf of defendants for use in the sentencing phases of criminal cases (from charging to clemency). The videos are typically short (5 to 10 minutes or so) nonfiction films that explore a defendant’s background, character, and family situation with the aim of raising factual and moral issues that support the argument for a shorter or more lenient sentence. Very few examples of mitigation videos are in the public domain and available for viewing. This article provides a complete analysis of the constituent elements of these videos, particularly their narrative structure. It raises strategic considerations that are pertinent to the decision to use a video during the sentencing process and explores questions of image ethics that can arise when a defendant’s children and parents are enlisted as video witnesses. Finally and most importantly, it addresses the hearsay challenges that not only present obstacles to the admission of sentencing videos in formal sentencing proceedings, but also impact the weight they are accorded in general